Spatial distribution of diphtheria cases during the 2022/2023 outbreak in Kano State, Northern Nigeria - Rayyan M. Garba; Zainab A. Umar; Zainab Abdulkadir; Usman Bashir; Rabiu I. Jalo; Yasir N. Jibril; Aminu A. Yusuf; Kabiru I. Gurama; Abdullahi K. Suleiman; Zainab U. Ibrahim; Sherifah Sheriff; Ibrahim D. Muhammad; et al. (PLoS ONE, 2026)
After decades of control, a nationwide diphtheria outbreak occurred in Nigeria in 2022, with approximately 75% of confirmed cases reported in Kano state, Nigeria. We assessed the spatial distribution of diphtheria cases in Kano state to identify disease clusters/hotspots. We used national surveillance data on 10,085 confirmed cases of diphtheria in Kano state from April 2022 to December 2023, accessed via the Nigerian Centre for Disease Control and Prevention website. Data were converted to CVS format and analyzed for spatial distribution of diphtheria cases using QGIS-LTR Version 3.34.11 . We found clustering of diphtheria cases in the eight metropolitan Local Government Areas (LGAs) of the state, where health facilities were also clustered. Ungogo LGA had the highest clustering of diphtheria cases but the least clustering of health facilities. This study enhances understanding of the spatial dynamics of diphtheria transmission in Nigeria and provides actionable insights for designing targeted interventions and strategies against hotspots to curb transmission and strengthen preparedness for future epidemics.